2022
DOI: 10.3389/fenvs.2022.949353
|View full text |Cite
|
Sign up to set email alerts
|

Niche expansion by indigenous fish species following the introduction of rainbow trout (Oncorhynchus mykiss) in a subtropical river system, upper Blyde River, South Africa

Abstract: The introduction of alien predatory fish such as rainbow trout (Oncorhynchus mykiss) can have a significant effect on indigenous fish communities such as altering the structure and dynamics of food webs. Quantifying the trophic niche utilised by the alien fish species is therefore important to aid our understanding of how their feeding strategies might aid establishment, define their functional role and inform on potential impacts. This study assessed food web interactions between fish communities in river rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Another example is the construction of the Three Gorges Reservoir, China, which led to a reduction in rheophilic fishes in the tributaries and increased competition with 18 non-native generalists that proliferated in the modified reservoir environment (Liao et al, 2018;Lin et al, 2018;Liu et al, 2019). Maimela et al (2022) revealed that adverse impacts on community structure and function were observed due to competition for food and space between O. mykiss and indigenous species in the upper Blyde River Catchment, South Africa. Psedudobarbus verloenii, a tropical rheophilic species, is reported to decline in South Africa due to reservoir construction.…”
Section: Temporal Habitat Displacement Of Rheophilic Species By Gener...mentioning
confidence: 99%
“…Another example is the construction of the Three Gorges Reservoir, China, which led to a reduction in rheophilic fishes in the tributaries and increased competition with 18 non-native generalists that proliferated in the modified reservoir environment (Liao et al, 2018;Lin et al, 2018;Liu et al, 2019). Maimela et al (2022) revealed that adverse impacts on community structure and function were observed due to competition for food and space between O. mykiss and indigenous species in the upper Blyde River Catchment, South Africa. Psedudobarbus verloenii, a tropical rheophilic species, is reported to decline in South Africa due to reservoir construction.…”
Section: Temporal Habitat Displacement Of Rheophilic Species By Gener...mentioning
confidence: 99%